Educação infantil do e no campo na Amazônia paraense: um olhar a partir do município de Soure - PANTOJA, Bianca Nazaré (2024)
The Course Completion Work (TCC) entitled “Early Childhood Education in and in the Countryside in the Amazon of Pará: a Look from the Municipality of Soure”, whose main objective was to discuss Early Childhood Education in and in the countryside in the municipality of Soure. Early Childhood Education in and in the countryside includes a diversity of people and populations living in rural areas of the country, it is an education that builds the foundations to combat an education model that simply reproduces, in rural territories, the dominant urban culture. For the research, we sought to understand the reality of Early Childhood Education in the countryside and in the Amazon of Pará. To do this, we mapped the educational service and investigated the challenges present in EIC in this region. The theoretical framework used in this work was Hage (2005 and 2019), Brandão (1981), Freitas and Reis (2019), Silva and Pasuch (2010), Silveira and Paludo (2014) and Rosemberg and Artes (2012). Through bibliographical review and documentary analysis, I gathered data that shows how educational assistance for children has been provided and what challenges they face so that they have access to quality education. The results indicate that even with several challenges to be faced, educational assistance for young children has been gradually improving, through public policies that value education and Brazilian diversity.